Raziskovanje etničnosti in manjšin na Madžarskem - na primeru institucionalizacije - Munda Hirnök, Katalin (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2006)
RESEARCH STUDIES OF ETHNICITY AND MINORITIES IN HUNGARY IN THE CASE OF INSTITUTIONALIZATION. The article focuses on the essential phenomena and tendencies in the development of institutionalization of research studies of ethnicity and minorities in Hungary ever since the 1st half of the 20th century, when the need of a social discipline as would deal with minorities appeared (or rather, the need to place this discipline within institutional framework), till the present day. The survey of research studies on the Porabje Slovenes, to which the last part of the article is dedicated, shows that the Slovene minority is faced with the problem of the lack of its own researchers (the lack of minority elite in general) of different scientific profiles (with the exception of ethnology and linguistics), as well as with the lack of institutional infrastructure.
Keywords: Hungary; Madžarska; narodne manjšine; raziskovalni projekti; znanstvenoraziskovalno delo; slovenska manjšina; Porabje; institucionalizacija